Handling Stunting as a Management Community Service - Agung Muliawan; Difari Afreyna Fauziah; Ahmad Nurdianyah; Arini Shufia Dwi Sukmawati; Muhammad Rijalus Sholihin (Medikun Publisher, 2024)
Stunting is a condition of chronic malnutrition caused by insufficient nutritional intake over a long period of time due to inadequate food supply to meet nutritional needs. Stunting is a problem that is difficult to solve if the factors causing stunting in each region cannot be controlled. Basically, the layer that interacts most intensively with patients diagnosed with stunting directly is the posyandu cadres who are the first counselors for mothers and children at the lowest level. The method used in this Collaborative Real Work Lecture (KKN) student service activity is counseling and training to improve the skills and role of the targets, namely posyandu and RDS cadres in the prevention and early detection program of stunting in children and toddlers. This activity aims to directly increase the role of posyandu cadres who are very close to the community in resolving stunting problems and indirectly to motivate the community to participate in paying attention to the growth and development of their children so that their growth and development can be optimal. It is hoped that the knowledge of Lampeji Village cadres and RDS members regarding stunting prevention will increase and the knowledge gained can be applied to the Lampeji Village community so that they can contribute to parenting and assisting children's growth and development